Identifikasi Cemaran Zat Pewarna Berbahaya Rhodamin B Pada Beberapa Produk Lipstik - Siti Cholifah; Lukky Jayadi (Journal Syifa Sciences and Clinical Research, 2022)
Rhodamine B is a synthetic dye used in industries such as paper and textile dyes. Rhodamine dye is prohibited from being used in cosmetic preparations because rhodamine is carcinogenic and can cause irritation and cancer in long-term use. This study aims to determine the presence of harmful dyes in lipstick cosmetic preparations. The method used in this research is using concentrated HCl reagent and 10% NaOH, this method is used as a test for the alleged presence of rhodamine in the sample. Positive results of the presence of rhodamine content were indicated by a change in the color of the sample which became dark orange after concentrated HCl was added and turned blue after 10% NaOH was added. Then continued by using the UV-Vis spectrophotometry method to determine the rhodamine levels in the sample. The samples used were 5 red lipsticks, from 5 samples that were tested, 1 sample was indicated which was indicated to contain rhodamine b because it changed color to orange when given concentrated HCl and blue when given 10% NaOH. Positive samples were samples with code C, after measuring with spectrophotometry, the results showed that the levels of Rhodamine in the sample were 0.009% in replication 1; 0.012% at replication 2 and 0.008 at replication 3.